(3GdJMaI GdZQhjI aj TQM GddeYI GdOeTbjIs - (3Bd NOGe, GdHGgdj, GdYaeGhj, GdfLaj, NVQ Hf TdGd Hf NWGH, J (B1255 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3cJGH GdUdGI GdeaSQ daI HGdOYGA hGdQMeI hGdGSJZaGQ hGdeJGHYI hMSf GdKfGA ef Gddg Ydi fHjg Udi Gddg Ydjg hSde GdeYdheh Yf chf GdMbjbI efgG GdGhd dTjhY GdGSJYeGd (B...s
(3BNQgG (B:s
... (3eG jJfGhd GdEbGeI cGdeQhj Yf Ydj hjYVOg GdGYJHGQ hGdJSGeM aj GOdI GdSff ceG b jSJaGO efg GdaMhi adjJCed ajeG bO SGbg Gddg JYGdi Edi YHOges
(3efShNI ef fSNI HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1/671s
(3GdPQjYI (B3 - 250 (1674)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis